Optimization of an immunoenzymatic (ELISA) assay for detecting ovine antibodies against Haemonchus contortus - Díaz, A.; Arenal, A.; França, Jessea; Gomes, Alda L.; Machado, Maria A.; Sossanovicz, M.; Yoshitani, Úrsula; Molento, M. B. (Cuban Journal of Agricultural Science, 2016)
Diseases originated by gastrointestinal nematodes are one of the most important causes of economic losses in animals, mainly in small ruminants. The objective of this study was to optimize an ELISA immunoenzymatic assay for Haemonchus contortus. For that, an extract of total proteins was extracted from a macerate of the adults of this nematode. Blood samples were taken of 48 sheep for obtaining the serum. The parameters of an immunoenzimatic (ELISA) assay were optimized. The best concentration for covering the antigen was 5 μg/mL. The best relationships between the signals of the positive and negative serums for serum dilution, the Anti-IgG and the bovine fetal serum were obtained in 1:300, 1:7000 and 0.25 %, respectively. The optimization of the parameters of this ELISA immunoenzymatic assay allowed the detection of IgG that recognize Haemonchus contortus with low unspecific interactions. This is the first study available on the optimization of an ELISA assay for Haemonchus contortus. Key words: optical density, IgG, Haemonchus contortus